Production Performance, Egg Quality and Intestinal Histology in Laying Hens Fed Dietary Dried Fermented Ginger - Incharoen, T.; Yamauchi, K. (International Journal of Poultry Science, 2009)
To evaluate the effect of dietary Dried Fermented Ginger (DFG) on production performance, egg quality and intestinal histology, 27 White Leghorn laying hens (24 weeks of age) were assigned into three groups of 9 birds each as follows: the control group was fed a basal diet (CP, 17%; ME, 2,850 kcal/kg) and the other groups were fed the basal diet supplemented with 1% or 5% DFG. Compared with the control, feed consumption tended to increase in DFG groups and increased significantly in the 1% DFG group (p<0.05). Hen-day egg production and egg mass are better in both DFG groups. Feed efficiency tended to be a little higher value in the DFG diets. There were no significant (p>0.05) differences in shell-breaking strength, shell thickness, shell ratio, albumen ratio, yolk ratio, yolk color and Haugh unit among the dietary treatments. Villus height, villus area, cell area and cell mitosis in all intestinal segments tended to be higher in DFG groups than in the control group and jejunal cell area of the 1% DFG group as well as jejunal cell mitosis of the both DFG groups showed significant increases. Moreover, the cells on the villus tip surface were protuberated in all DFG groups, resulting in a rough surface. In addition, segmented filamentous bacteria were observed in the ileum of the 5% DFG group. These results suggest that dietary DFG increase the production performance of layer chickens due to hypertrophy of intestinal villi and epithelial cells at 1% DFG.